The complete mitochondrial genome of the Toxopneustes pileolus Lamarck, 1816 (Echinoidea: Camarodonta: Toxopneustidae) and phylogenetic analysis - Xinyuan Wang; Weijian Guo (Mitochondrial DNA. Part B. Resources)
In this study, we report the complete mitochondrial genome sequence of Toxopneustes pileolus (Lamarck, 1816), which is the first complete mitochondrial genome of this genus Toxopneustes. The mitochondrial genome is 15,711 bp in length and includes 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes, and one non-coding control region (D-loop). Phylogenetic analysis based on mitochondrial genomes suggested a potential close relationship between the genus Toxopneustes and the genus Lytechinus. This study provided valuable genetic data for T. pileolus and contributed to the exploration of the phylogenetic relationships within the family Toxopneustidae.